2014
DOI: 10.1016/j.ijscr.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Fatal skin and soft tissue infection of multidrug resistant Acinetobacter baumannii: A case report

Abstract: INTRODUCTIONAcinetobacter baumannii is usually associated with respiratory tract, urinary tract and bloodstream infections. Recent reports suggest that it is increasingly causing skin and soft tissue infections. It is also evolving as a multidrug resistant organism that can be difficult to treat. We present a fatal case of multidrug resistant A. baumannii soft tissue infection and review of relevant literature.PRESENTATION OF CASEA 41 year old morbidly obese man, with history of alcoholic liver disease present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…For smoking, the top ML feature Acinetobacter was only at rank 91 th according to the t-test and other 6 genera were ranked below 100. Species within the Acinetobacter genus have been linked with respiratory and bloodstream infections which could explain their usefulness in smoking prediction with this being reflected in the leg microbiome (47). This indicates the set of most predictive genera inferred by our EAI approach can differ from the ones highlighted by a standard statistical approach that consider each genus independently.…”
Section: Discussionmentioning
confidence: 97%
“…For smoking, the top ML feature Acinetobacter was only at rank 91 th according to the t-test and other 6 genera were ranked below 100. Species within the Acinetobacter genus have been linked with respiratory and bloodstream infections which could explain their usefulness in smoking prediction with this being reflected in the leg microbiome (47). This indicates the set of most predictive genera inferred by our EAI approach can differ from the ones highlighted by a standard statistical approach that consider each genus independently.…”
Section: Discussionmentioning
confidence: 97%
“…Multidrug resistance have been frequently reported in recent days and threatens the effectiveness of successful treatment of infections especially using empiric antibiotics. The incidence of MDR microbes is on the rise over the past decades, meanwhile many studies still advocate for early broad-spectrum empiric or combination antibiotic therapy [ 9 ]. Godebo et al in a study to determine multidrug resistance rate of bacterial isolates that caused wound infections in a specialised centre in SSA, showed that overall MDR among gram positive and gram negative bacterial isolates were 77 and 59.3% respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common pathogens isolated from cultures are gram positive organisms like ÎČ -hemolytic group A streptococcus, Staphylococcus aureus , bacillus species, enterococci species and gram negative organisms such as Klebsiella pneumonia, Pseudomonas aeroginosa , Serratia species , Escherichia coli , Clostridium species, Fusobacterium species, and Prevotella species [ 2 , 7 , 8 ]. NF carries a high morbidity and mortality especially when diagnosed late [ 5 , 9 ] necessitating prompt diagnosis and timely treatment with radical surgical debridement and empiric broad spectrum antibiotic therapy [ 2 , 10 ]. The mortality rate due to NF ranges from 25 to 35% despite empiric broad-spectrum antibiotic therapy and surgical debridement [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further bacteria associated with wound infections in immunocompromised patients or after trauma respectively surgery, were identified in our specimen: Acinetobacter pitii [ 27 ], [ 28 ], [ 29 ] (a Gram-negative non-fermenting rod of growing clinical importance), Acinetobacter ursingii [ 30 ] (a species related to Acinetobacter baumannii ), Leclercia adecarboxylata [ 31 ], Citrobacter brakii [ 32 ] (both are Gram-negative rods belonging to the family of Enterocerobacteriacea), Bacillus cereus [ 33 ] and Bacillus pumilus [ 34 ], Gram-positive spore-forming rods, which are ubiquitously found in the environment and mostly regarded as contaminants. Brevibacillus parabrevis was detected in one case (patient ID 1).…”
Section: Discussionmentioning
confidence: 99%